2018
DOI: 10.3389/fphar.2018.01006
|View full text |Cite
|
Sign up to set email alerts
|

3-Chloro-N′-(2-hydroxybenzylidene) benzohydrazide: An LSD1-Selective Inhibitor and Iron-Chelating Agent for Anticancer Therapy

Abstract: Despite the discovery and development of novel therapies, cancer is still a leading cause of death worldwide. In order to grow, tumor cells require large quantities of nutrients involved in metabolic processes, and an increase in iron levels is known to contribute to cancer proliferation. Iron plays an important role in the active site of a number of proteins involved in energy metabolism, DNA synthesis and repair, such as ribonucleotide reductase, which induce G0/S phase arrest and exert a marked antineoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Assay was performed as previously described using a KDM4A Inhibitor Enzymatic Assay KIT (Epi-C, Naples, Italy) (Franci et al, 2017;Sarno et al, 2018), and by JMJD2A (KDM4A) Homogeneous Assay Kit (#50413; BPS Bioscience, Milan, Italy). In KDM4A Inhibitor Enzymatic Assay KIT by Epi-C, the compounds (6 µL) were incubated for 30 min at 37 • C with 24 µL of enzymatic solution in a 96-well black half-area plate.…”
Section: Enzymatic Assaymentioning
confidence: 99%
“…Assay was performed as previously described using a KDM4A Inhibitor Enzymatic Assay KIT (Epi-C, Naples, Italy) (Franci et al, 2017;Sarno et al, 2018), and by JMJD2A (KDM4A) Homogeneous Assay Kit (#50413; BPS Bioscience, Milan, Italy). In KDM4A Inhibitor Enzymatic Assay KIT by Epi-C, the compounds (6 µL) were incubated for 30 min at 37 • C with 24 µL of enzymatic solution in a 96-well black half-area plate.…”
Section: Enzymatic Assaymentioning
confidence: 99%
“…Furthermore, a tissue microarray analysis from 75 breast cancer patients revelated that high G9a expression and low hephaestin expression are associated with poor prognosis [ 78 ]. Interestingly, iron-chelating agents including deferoxamine (DFO), deferasirox (DFX), and their synthetic derivatives inhibit epigenetic JumonjiC domain-containing histone lysine demethylases (JmjC KDMs) which are Fe(II)/2-oxoglutarate-dependent oxygenases that are also involved in transcriptional regulation and DNA repair [ 79 , 80 ]. The first demonstration has been performed by Cao et al, showing that DFO induced a significant increase in global histone methylation in colorectal cancer, leading to the dysregulation of many cell growth-related genes [ 81 ].…”
Section: Iron and Cscmentioning
confidence: 99%
“…Intracellular iron accumulation may accelerate lung tumorigenesis and development ( Aleman et al, 2002 ). Reducing iron levels with DFX, and its analogs, inhibits tumor growth by limiting iron provision ( Sarno et al, 2018 ). These results were favored by researchers who demonstrated that iron chelators can suppress the growth of human lung tumor xenografts ( Lui et al, 2013 ).…”
Section: Ferroptosis In Relevant Malignant Tumorsmentioning
confidence: 99%